Effect of use of olive mill wastewater for moistening of dry beet pulp in diets on fattening performance of lambs, carcass characteristics and meat quality - Benbati M.; El Hansali M.; El Fazazi K.; Chafki L.; Haddioui A.; Keli A. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The objective of this study was to evaluate the effect of use of olive mill wastewater (OMW) for moistening dry beet pulp in lambs’ diet on fattening performance, carcass characteristics and meat quality. OMW were used to replace partially or totally water used for moistening the dry beet pulp (DBP). Twenty four crossbreed lambs “D’man x Boujaad” were randomly assigned to 4 treatments: T1 containing 27% alfalfa, 11% barley straw and 62% barley grain; T2 containing 26% alfalfa, 10% straw, 32% barley grain and 32% PSB (humidified with 100% water); T3 containing 26% alfalfa, 10% straw, 32% barley and 32% PSB (humidified with 50% water and 50% OMW), T4 containing 26% alfalfa, 10% straw, 32% barley grain and 32% PSB (humidified with 100% OMW). The fattening trial was lasted 70 days after 7-days of adaptation period and lambs were weighed at the beginning and at the end of the trial, and fortnightly. At the end of the trial, lambs were slaughtered and the carcass dressing percentage (CDP), fatness (1-5 scale), conformation (SEUROP system), ruminal pH, pH of meat at 0 and 24h postmortem, fat deposition (mesenteric and pelvic fat) were determined. The use of OMW for moistening of dry beet pulp in the lamb diet did not affect the average daily gain, ruminal pH, cold CDP, fatness, conformation, pH of meat at 0 and 24h postmortem and fat deposition (mesenteric and pelvic fat). The average daily gain of lambs was 214.5, 236.8, 219.2 and 217.6 g/d for T1, T2, T3 and T4, respectively. The cold CDP was 47.7, 47.3, 47.3 and 47.7 for T1, T2, T3 and T4, respectively.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)